Gender differences in specialty preference and mismatch with real needs in Japanese medical students - Fukuda, Yoshiharu (BioMed Central, 2010)
BACKGROUND: The shortage of doctors and maldistribution among specialties are of great concern in the Japanese health care system. This study investigated specialty preference in medical students of one university, and examined gender differences and compared their preference with real needs. METHODS: We conducted a self-administered questionnaire including specialty preference in all students of one medical university. Preference was assessed by the five-level probability of their future choice: 1 = very low, 2 = low, 3 = moderate, 4 = high, and 5 = very high. The proportion of 4 or 5 was calculated as the preference rate. The real needs (magnitude of doctor shortage) in the prefecture were drawn from two different surveys. The relationship between the sex-specific preference rate by specialty and real needs was assessed by Spearman's correlation coefficient. RESULTS: Internal medicine showed the highest preference rate, followed by general surgery, pediatrics, and emergency medicine. There was no significant correlation between the preference rates of men and women (r = 0.27, p = 0.34). The preference rates for general surgery, orthopedics, neurosurgery, and emergency medicine were significantly higher in men than in women, while those of obstetrics & gynecology, pediatrics, and dermatology were significantly higher in women. The magnitude of doctor shortage by specialty from two surveys were significantly correlated with the total preference rate and men's preference rate (r = 0.54 to 0.74), but not with women's preference rate (r = 0.06 and 0.32). CONCLUSIONS: This study elucidated not only gender differences in specialty preference but also the relationship to real needs. Critical gender differences and mismatch with real needs were found in women. In addition to traditional gender roles and insufficient support for women's participation in Japan, gender differences and mismatch influence the current and future maldistribution of specialties. Systematic changes in the working environment in medical society are required to solve these problems.